Penerapan Media Pembelajaran Audio Visual Berbasis Canva untuk Meningkatkan Motivasi dan Hasil Belajar Siswa dalam Mata Pelajaran TIK - Virizki, Asep Piar; Zakaria, Yoyo (Indo-MathEdu Intellectuals Journal, 2024)
Mathematics learning activities at SMP Negeri 4 Ciawigebang in general still use textbooks or package books as one of the references used. The school where the research was conducted still uses package books as a learning medium and the method used uses the lecture method, so that in this case Mathematics learning becomes monotonous and less interesting and less motivating to students. This research aims to improve mathematical skills by using Scratch media. The research method used is quantitative with a quasi-experimental type using a research design, namely pretest posttest control design which was carried out at SMP Negeri 4 Ciawigebang. The population used in this study is students in grades 8b and 8e with a total of 54 students. Data collection techniques through observation, tests and questionnaires. The analysis of research data uses a t-test. The results of the analysis showed that there was a change in the improvement of student learning outcomes after the application of scratch learning media to the material of the two-variable linear equation system in mathematics in grade VII of SMP Negeri 4 Ciawigebang